2018
DOI: 10.1371/journal.pone.0207080
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and population genetic analyses reveals cryptic speciation in the Bombus fervidus species complex (Hymenoptera: Apidae)

Abstract: Bumble bees (Bombus Latrielle) are significant pollinators of flowering plants due to their large body size, abundant setae, and generalist foraging strategies. However, shared setal coloration patterns among closely and distantly related bumble bee species makes identification notoriously difficult. The advent of molecular genetic techniques has increased our understanding of bumble bee evolution and taxonomy, and enables effective conservation policy and management. Individuals belonging to the North America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Some species historically described by discrete colour differences have been revealed to be conspecific, as discrete morphologies can be generated from diallelic Mendelian traits (Owen & Plowright, ; Rasmont et al ., ; De Meulemeester et al ., ). Failure to fully sort ancestral colour polymorphisms by species also has led to false inferences of species boundaries (Hines, ; Carolan et al ., ; Koch et al ., ; Williams et al ., ). In this instance, bifarius s.s. is a monomorphic red‐banded bee species and nearcticus is a polymorphic species that follows a continuum of variation from black to red from west to east (excepting island populations).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some species historically described by discrete colour differences have been revealed to be conspecific, as discrete morphologies can be generated from diallelic Mendelian traits (Owen & Plowright, ; Rasmont et al ., ; De Meulemeester et al ., ). Failure to fully sort ancestral colour polymorphisms by species also has led to false inferences of species boundaries (Hines, ; Carolan et al ., ; Koch et al ., ; Williams et al ., ). In this instance, bifarius s.s. is a monomorphic red‐banded bee species and nearcticus is a polymorphic species that follows a continuum of variation from black to red from west to east (excepting island populations).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, coloration of thoracic and abdominal setae can be highly variable, leading to a historical focus on colour traits for species diagnosis. Colour patterns, however, can be poor traits for diagnosis in bumblebees (Carolan et al ., ; Hines & Williams, ; Koch et al ., ). One of the major reasons for this colour variation is Müllerian mimicry, which has driven many Bombus species towards nearly identical colour patterns within a geographical region, while promoting diverse colour forms within species across their distributions (Williams, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…vancouverensis nearcticus Handlirsch, 1888 were recognized as molecularly dis-tinct from B. bifarius Cresson, 1878(Ghisbain et al 2020; B. sylvicola Kirby, 1837 was recognized as a subspecies of the Holarctic B. lapponicus (Fabricius, 1793); and a new species of Pyrobombus with close affinities to B. lapponicus, B. interacti Martinet, Brasero & Rasmont, 2019 was described from Alaska (Martinet et al 2019). At this point, 48 species of bumble bee are now recognized in North America north of Mexico, though the taxonomic status of some species is still unresolved (e.g., Yanega 2013;Koch et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Variation is broadly present in bees. Bumble bees, for example, are known for presenting high variability in its coloration pattern (e. g. Carolan et al, 2012;Huang et al, 2015;Koch et al, 2018). Color variation in Eucerini bees was reported by Grando et al, (2018) that found two distinct color patterns in sympatric populations of Melissodes nigroaenea in Brazil.…”
Section: Discussionmentioning
confidence: 99%